Pseudomonas aeruginosa Outer Membrane Vesicles Triggered by Human Mucosal Fluid and Lysozyme Can Prime Host Tissue Surfaces for Bacterial Adhesion - Metruccio, Matteo M. E.; Evans, David J.; Gabriel, Manal M.; Kadurugamuwa, Jagath L.; Fleiszig, Suzanne M. J. (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa is a leading cause of human morbidity and mortality that often targets epithelial surfaces. Host immunocompromise, or the presence of indwelling medical devices, including contact lenses, can predispose to infection. While medical devices are known to accumulate bacterial biofilms, it is not well understood why resistant epithelial surfaces become susceptible to P. aeruginosa. Many bacteria, including P. aeruginosa, release Outer Membrane Vesicles (OMVs) in response to stress that can fuse with host cells to alter their function. Here, we tested the hypothesis that mucosal fluid can trigger OMV release to compromise an epithelial barrier. This was tested using tear fluid and corneal epithelial cells in vitro and in vivo. After 1 h both human tear fluid, and the tear component lysozyme, greatly enhanced OMV release from P. aeruginosa strain PAO1 compared to PBS controls (~100 fold). TEM and SDS-PAGE showed tear fluid and lysozyme-induced OMVs were similar in size and protein composition, but differed from biofilm-harvested OMVs, the latter smaller with fewer proteins. Lysozyme-induced OMVs were cytotoxic to human corneal epithelial cells in vitro and murine corneal epithelium in vivo. OMV exposure in vivo enhanced Ly6G/C expression at the corneal surface, suggesting myeloid cell recruitment, and primed the cornea for bacterial adhesion (~4-fold, P < 0.01). Sonication disrupted OMVs retained cytotoxic activity, but did not promote adhesion, suggesting the latter required OMV-mediated events beyond cell killing. These data suggest that mucosal fluid induced P. aeruginosa OMVs could contribute to loss of epithelial barrier function during medical device-related infections.